He Situation Of The Food Industry In The Fergana Valley Regions During World War II - M. Khojamov, M. Khojamov (Indonesian Journal Publisher, 2020)
In this article, changes and problems in the food industry of Uzbekistan during the Second World War are analyzed on the example of the regions of the Fergana Valley. The main focus of the article is on the state of the food industry in the region, the specific problems in the system, the negative impact of the war on the food industry of the Ferghana Valley and its solutions.